Jawabanmu

2014-03-24T10:18:48+07:00
1.) (hogof)(x) = hog (2-3)
               = h (-1^2 + 1)
               =3(1) = 3

2.) (fog)(x) = f (x+2 / x-1)
                 = 2 (x+2 / x-1) - 1
                 = (2x+4 / x-1) - 1
                 = 2x+4-x-1 / x-1
                 = x-3 / x-1
1 1 1
2014-03-24T11:39:56+07:00
1. (hogof)(3) = ?
f(x)= 2 - x
g(x) = x^{2}+1
h(x)=3x


hogof (x) = h(g(f(x)))
             = h(g(2-x))
             = h (  (2-x)^{2} + 1)
             = h ( 4 - 4x +  x^{2} + 1)
             = h ( 5 - 4x +
 x^{2} )
             = 3 ( 5 - 4x +  x^{2} )
             = 15 - 12x + 3 x^{2}
hogof (3) = 15 - 12(3) + 3  (3^{2})
              = 15 - 36 + 27
              = 6

2.
(fog)(x) = ?
f(x)= 2x-1
g(x) =  \frac{x+2}{x-1}

fog (x) = f(g(x))
          = f ( \frac{x+2}{x-1} )
           = 2(
 \frac{x+2}{x-1} ) - 1
           =  \frac{2x+4}{x-1} - ( \frac{x-1}{x-1} )
           =
 \frac{x+5}{x-1}

3. (fog)(x) = ?
f(x+2) =  \frac{x+1}{2x-2}
g(x) = 3x-4


f^{-1} (x) = x-2
f(x) =  \frac{(x-2)+1}{2(x-2)-2}
f(x) =  \frac{x-1}{2x-6}

fog(x) = f(g(x))
         = f(3x-4)
         =  \frac{(3x-4)-1}{2(3x-4)-6}
         =  \frac{3x-5}{6x-14}

semoga membantu :) jadikan yang terbaik ya!